Charge transfer interaction of organic p-acceptors with the anti-hyperuricemic drug allopurinol: Insights from IR, Raman, 1H NMR and 13C NMR spectroscopies - Refat Moamen S.; Saad Hosam A.; Adam Abdel Majid A.; Al-Omar Mohamed A.; Naglah Ahmed M. (Acta Pharmaceutica)
The topic of charge-transfer (CT) complexation of vital drugs has attracted considerable attention in recent years owing to their significant physical and chemical properties. In this study, CT complexes derived from the reaction of the anti-hyperuricemic drug allopurinol (Allop) with organic p-acceptors [(picric acid (PA), dichlorodicyanobenzoquinone (DDQ) and chloranil (CHL)] were prepared, isolated and characterized by a range of physicochemical methods, such as IR, Raman, 1H NMR and 13C NMR spectroscopy. The stoichiometry of the complexes was verified by elemental analysis. The results show that all complexes that were formed were based on a 1:1 stoichiometric ratio. This study suggests that the complexation of Allop with either the DDQ or CHL acceptor leads to a direct p®p* transition, whereas the molecules of Allop and PA are linked by intermolecular hydrogen- bonding interactions.